2010
DOI: 10.1007/s10763-010-9261-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Culture on High-School Students’ Question-Asking Ability Resulting From an Inquiry-Oriented Chemistry Laboratory

Abstract: In order to cope with complex issues in the science-technologyenvironment-society context, one must develop students' high-order learning skills, such as question-asking ability (QAA), critical thinking, evaluative thinking, decisionmaking, and problem-solving capabilities within science education. In this study, we are concerned with evaluating the effect of student-teacher interaction-which is regulated by culture and traditions-on the QAA in science classroom in general and, specifically in our case, in che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 32 publications
(47 reference statements)
2
14
0
Order By: Relevance
“…Such findings are of concern as there is little argument that the opportunity to ask questions is essential in facilitating the development of problem solving skills (Dkeidek, Mamlok-Naaman, & Hofstein, 2011). The results of this study support this with the findings showing that nursing students need opportunities to ask questions and this is best done within a non-threatening environment.…”
Section: Confidencesupporting
confidence: 57%
“…Such findings are of concern as there is little argument that the opportunity to ask questions is essential in facilitating the development of problem solving skills (Dkeidek, Mamlok-Naaman, & Hofstein, 2011). The results of this study support this with the findings showing that nursing students need opportunities to ask questions and this is best done within a non-threatening environment.…”
Section: Confidencesupporting
confidence: 57%
“…The Jewish chemistry teachers in this study showed comparably more modern educational beliefs, as it was documented also in Dkeidek et al (2010) and Dkeidek et al 2012) concerning the students' perception of chemistry laboratory classroom learning environment and the effect of teacher-student interaction and support on developing questioning ability among the students. Taking into consideration the characteristics of educational environments in more individualistic vs. collectivistic societies (Greenfield, 1999;Hofstede, 1980;Trianidis, 1995), also from this study it can be suggested that the Jewish sector is more according towards an individualistic paradigm where the Arabic sector is applying a stronger collectivist philosophy.…”
Section: Discussionsupporting
confidence: 62%
“…However, in their study it was not clear how big this influence was compared to the influence of the teacher education system and the socio-economic circumstances the educational system is operating in. It can be inferred from the results of the current study, as well as from the studies by Dkeidek et al (2010Dkeidek et al ( , 2012, that culture is a very important and often underestimated factor on understanding science teachers' beliefs, their influence on the teachers' classroom behaviour and the related effects on students' learning. Current research revealed that teachers' instructional practices affect minority students' achievements, attitudes, and careers (Kanter & Konstantopoulos, 2010).…”
Section: Discussionmentioning
confidence: 63%
“…Several studies have further emphasized the advantages of involving students in peer-assessment activities, including stimulating the self-reflection and higher order thinking of students (Dkeidek, Mamlok-Naaman, & Hofstein, 2011;Prins et al, 2005;Yu, Liu, & Chan, 2005).…”
Section: Peer Assessmentmentioning
confidence: 99%